2013
DOI: 10.1158/1940-6207.capr-12-0281
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Biologically Active Colonic Tissue Levels of Curcumin Achieved After Oral Administration—A Clinical Pilot Study Including Assessment of Patient Acceptability

Abstract: Curcumin, the main constituent of turmeric, is suspected to possess cancer chemopreventive properties. Pharmacokinetic and pharmacodynamic parameters have been reported, but few data exist describing whether methodologies are suitably robust for curcuminoid detection in colonic biopsy specimens. Information on the acceptability of prolonged administration of daily curcumin is not available. This is of vital importance to implement chemoprevention strategies. This study aimed to quantify levels of curcuminoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 26 publications
2
58
0
3
Order By: Relevance
“…In support of this, a preceding study in rats by the same group revealed that, 24 hour after per gavage administration of 400 mg of curcumin, approximately 40% of curcumin was present in the gastrointestinal tract and that curcumin levels in blood, liver, and kidneys were below the limit of detection (,5 mg/ml or g tissue, equivalent to 13 mM) (Ravindranath and Chandrasekhara, 1980). Furthermore, relatively high curcumin concentrations have been found in colorectal mucosa of patients after oral intake (Garcea et al, 2005;Carroll et al, 2011;Irving et al, 2013) and in feces as well as intestinal and colonic mucosa in rats after 1 week of dietary curcumin intake (Perkins et al, 2002). Given the very low curcumin levels in healthy tissue, it is likely that the accumulation of curcumin in nonenteral tumor tissue will follow a similar pattern.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, a preceding study in rats by the same group revealed that, 24 hour after per gavage administration of 400 mg of curcumin, approximately 40% of curcumin was present in the gastrointestinal tract and that curcumin levels in blood, liver, and kidneys were below the limit of detection (,5 mg/ml or g tissue, equivalent to 13 mM) (Ravindranath and Chandrasekhara, 1980). Furthermore, relatively high curcumin concentrations have been found in colorectal mucosa of patients after oral intake (Garcea et al, 2005;Carroll et al, 2011;Irving et al, 2013) and in feces as well as intestinal and colonic mucosa in rats after 1 week of dietary curcumin intake (Perkins et al, 2002). Given the very low curcumin levels in healthy tissue, it is likely that the accumulation of curcumin in nonenteral tumor tissue will follow a similar pattern.…”
Section: Tablementioning
confidence: 99%
“…Clinical trials have reported patient discontent and withdrawal of patients from the high dosage cohorts solely due to the discomfort they experienced when ingesting a large amount of curcumin pills Irving et al, 2013).…”
Section: •-mentioning
confidence: 99%
“…C3 complex, collectively known as curcuminoids, is a standardized preparation (Sabinsa) of three curcuminoids-curcumin (76.07%), demethoxycurcumin (DMC; 20.28%), and bisdemethoxycurcumin (3.63%). The safety and efficacy of C3 complex is established in clinical trials (6)(7)(8). DMC and bisdemethoxycurcumin, natural demethoxy derivatives of curcumin, possess anti-inflammatory, and antiproliferative properties and are more stable than curcumin in serum (9).…”
Section: Introductionmentioning
confidence: 99%
“…Z těchto studií vyplývá, že při per os podání se kurkumin dostává do střevní tkáně v množství, které může mít bio logický účinek [25], a je v ní detekovatelný i 40 hod po jeho posledním podání. Prokázána byla také bezpeč-nost a dobrá tolerance kurkuminu až do dávky 3,6 g denně, u ně kte rých pa cientů byla ale léčba provázena slabými gastrointestinálními obtížemi [26,27].…”
Section: Klinické Studie Hodnotící Protinádorový účInek Kurkuminuunclassified